C3GN associated with deletion in CHFR1 and CHFR3 genes: a case report - Kandari, Sharon; Ravikant; Rohit Puri; Cheriyan, Anil; Gangdev, Abhay Nalinbhai; Ahlawat, Parul (International Journal of Research in Medical Sciences, 2025)
C3GN is a unique abnormality that commonly occurs due to an abnormal alternative path of the complement complex. This is distinguished by precipitation of mainly the C3 factor of complement along with minimal deposit of immunoglobulin in the mesangial, subepithelial, and subendothelial areas of glomeruli. It is seen that most of the mutations that are pathogenic happen in C3, complement factor B (CFB), complement factor H (CFH), complement factor I, along with CFHR5. Some other associations are also found that could lead to this disorder, such as autoantibodies against C3 nephrotic factor, C5 nephritic factor, anti-CFB autoantibodies, along with anti-CHF antibodies. Atypical HUS occurs due to abnormality in different components of the alternate pathway, such as complement factor F, and autoantibodies against anti-CFH caused by CFHR 1 and 3 deletions. Here we narrate a rare occurrence of C3GN related to mutation in CFHR1 and 3 in a young female and her mother who presented to us for renal transplant as prospective recipient with her mother as donor.